2015
DOI: 10.1002/cam4.484
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of RND3/RhoE in glioblastoma patients promotes tumorigenesis through augmentation of notch transcriptional complex activity

Abstract: Activation of Notch signaling contributes to glioblastoma multiform (GBM) tumorigenesis. However, the molecular mechanism that promotes the Notch signaling augmentation during GBM genesis remains largely unknown. Identification of new factors that regulate Notch signaling is critical for tumor treatment. The expression levels of RND3 and its clinical implication were analyzed in GBM patients. Identification of RND3 as a novel factor in GBM genesis was demonstrated in vitro by cell experiments and in vivo by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…Genetic deletion of RND3 promoted mouse ependymal epithelia proliferation, which in turn led to aqueduct stenosis and hydrocephalus development [20]. We also demonstrated an inhibitory role of RND3 in GBM tumorigenesis through targeting Notch signaling [8]. Similar observations were detected in lung cancer and squamous cell carcinomas by other groups [21, 22], clearly indicating the important role of RND3 in tumorigenesis.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Genetic deletion of RND3 promoted mouse ependymal epithelia proliferation, which in turn led to aqueduct stenosis and hydrocephalus development [20]. We also demonstrated an inhibitory role of RND3 in GBM tumorigenesis through targeting Notch signaling [8]. Similar observations were detected in lung cancer and squamous cell carcinomas by other groups [21, 22], clearly indicating the important role of RND3 in tumorigenesis.…”
Section: Introductionsupporting
confidence: 77%
“…We also demonstrated that downregulation of RND3 promoted GBM cell proliferation and tumorigenesis [8]. …”
Section: Introductionmentioning
confidence: 99%
“…The role of RhoE in cancer is currently controversial [ 37 , 38 , 39 ]. In human glioblastoma, RND3 expression was found to be significantly decreased, which caused increased Notch-pathway activity and enhanced glioma cell proliferation [ 40 ]. RND3 functioned as a negative regulator of the Notch pathway by promoting the ubiquitination and degradation of Notch transcriptional complex [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human glioblastoma, RND3 expression was found to be significantly decreased, which caused increased Notch-pathway activity and enhanced glioma cell proliferation [ 40 ]. RND3 functioned as a negative regulator of the Notch pathway by promoting the ubiquitination and degradation of Notch transcriptional complex [ 40 ]. In this study, RND3 was upregulated after EBLN1 silencing in OL cells, and MAML2 , coded a coactivator for Notch protein, was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…The cell growth-inhibiting effect of RND3 overexpression has been demonstrated in esophageal squamous cell carcinoma cells, 23 while RND3 knockdown was found to enhance cell proliferation in glioblastoma cells and neural stem cells. 24,25 We therefore investigated whether miR-182-5p and miR-96-5p would inuence HCC cell growth in vitro by targeting RND3. Our cell viability and proliferation assay results both suggested that RND3 OE or TC-S 7001 treatment partially attenuated the cell proliferation-promoting effect of miR-182-5p or miR-96-5p agomir treatment in HCC cells in vitro (Fig.…”
Section: Mir-182-5p or Mir-96-5p Increased Hcc Cell Mobility In Vitromentioning
confidence: 99%